Kajian Interaksi Obat pada Resep Polifarmasi Dokter Spesialis Dalam Periode April 2024 di Salah Satu Apotek di Kota Bandung - Annisa Maulida Azzahra; Yasmiwar Susilawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Drug interaction is a change in the effect of a drug due to the presence of other drugs taken simultaneously, which will cause a decrease in the therapeutic effect of the drug and toxicity in the body can increase. Changes in drug effects due to drug interactions vary greatly between individuals because they are influenced by various factors such as dose, drug levels in the blood, route of drug administration, drug metabolism, duration of therapy and patient characteristics. The potential for drug interactions can occur, one of which is in patients who take a large number of drugs simultaneously or Polypharmacy. Therefore, this study is related to the problem of drug interactions that occur due to Polypharmacy Prescriptions from internal medicine specialists at One of the Pharmacies in Bandung City which really needs to be considered, especially by a pharmacist. The results can be concluded that there are 22 drug interactions originating from 69 prescriptions with details of 10 minor interactions, 11 moderate interactions, and 1 major interaction. This shows that of the 69 prescriptions that have been studied, only 31.88% have interactions with minor, moderate, and major categories.